Influence Of Aviation Fuel On The Room Temperature And Post-Fire Compression Properties Of Sandwich Composite Materials - Hassan, Muhammad Addin (Universiti Sains Malaysia, 2018)
The main purpose of this final year project is to investigate the influence of aviation fuel on the room temperature and post-fire compression properties of sandwich composite. The materials used to fabricate sandwich composite is E-glass fibre, plastic core and epoxy matrix. The method used to fabricate composite is wet hand lay-up. In order to find the properties of sandwich composite, the specimen undergo immersion test and post-fire compression test. The aviation fuel is used in immersion test to determine how it will influence the properties of sandwich composite. For post-fire compression test, the specimen is heated with fire torch and then compressed using Instron testing machine (UTM). The experimental burn-off testing was conducted in order to calculate the fibre volume fraction of sandwich composite materials. It is found that the fibre volume fraction of sandwich composite is around 48%. Sandwich composite in biofuel has higher moisture absorption percentage compared to kerosene. The compression testing between normal and immersed sandwich composite was conducted and it is found that the compressive properties of immersed composite decrease as the bonding between fibre and matrix become weak. For post-fire compression testing, the compressive strength reduced with different heat exposure time. It was found that there are no significant changes in compressive strength in room temperature and high temperature for all specimen being immersed in aviation fuel.